PENGARUH SERVANT LEADERSHIP DAN KOMUNIKASI TERHADAP KINERJA DENGAN KOMITMEN ORGANISASI SEBAGAI VARIABEL MODERASI PADA PEGAWAI KANTOR PELAYANAN PAJAK PRATAMA WONOSARI (Jurnal Riset Mahasiswa, 2024)
This study aims to determine how much influence servant leadership and communication have on performance moderated by organizational commitment to KPP Pratama Wonosari employees. The method used in this study is a quantitative method, with data collection using a questionnaire. There were 65 KPP Pratama Wonosari employees in this study. The validity convergent test shows the statement that this study is valid, and the reliability test with Cronbach's Alpha is declared reliable. This study uses structural model analysis. The results of the analysis show that: (1) Servant Leadership has a positive effect on employee performance of 0.005. (2) Communication has a positive effect on employee performance of 0.006. (3) organizational commitment does not moderate servant leadership on employee performance with a value of 0.145. (4) organizational commitment moderate’s communication on employee performance by 0.035
Keywords: servant leadership; communication; performance; organizational commitment